2018
DOI: 10.15252/emmm.201708657
|View full text |Cite
|
Sign up to set email alerts
|

Role of NKp46 + natural killer cells in house dust mite‐driven asthma

Abstract: House dust mite (HDM)‐allergic asthma is driven by T helper 2 (Th2) lymphocytes, but also innate immune cells control key aspects of the disease. The precise function of innate natural killer (NK) cells during the initiation and propagation of asthma has been very confusing, in part because different, not entirely specific, strategies were used to target these cells. We show that HDM inhalation rapidly led to the accumulation of NK cells in the lung‐draining lymph nodes and of activated CD69+ NK cells in the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 60 publications
2
15
0
Order By: Relevance
“…In this model, Ncr1 iCre/+ R26 DTA/+ and R26 DTA/+ adult littermates had similar numbers of lung ILC2s ( Figure 7A) and the same magnitude of AAD ( Figure 7, B-E). Our results agreed with a recently published study that also used Ncr1 iCre R26 DTA mice to show a lack of any meaningful involvement of NK cells in adult OVA-and house dust mite extract-based (HDM-based) models of AAD (22). Taken together, our data showed that NK cells are redundant for allergen-driven, DEP-free AAD in adult mice.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In this model, Ncr1 iCre/+ R26 DTA/+ and R26 DTA/+ adult littermates had similar numbers of lung ILC2s ( Figure 7A) and the same magnitude of AAD ( Figure 7, B-E). Our results agreed with a recently published study that also used Ncr1 iCre R26 DTA mice to show a lack of any meaningful involvement of NK cells in adult OVA-and house dust mite extract-based (HDM-based) models of AAD (22). Taken together, our data showed that NK cells are redundant for allergen-driven, DEP-free AAD in adult mice.…”
Section: Resultssupporting
confidence: 92%
“…We also observed that NK cells were redundant in models that rely exclusively on allergens to elicit AAD. This is consistent with a recent publication that used Ncr1 iCre R26 DTA mice to report no role of NK cells in adult allergen-driven AAD (22).…”
Section: Methodssupporting
confidence: 92%
“…NK cells have an immunoregulatory role in many inflammatory pathologies and their involvement in asthma remains highly controversial in the literature. The development of house dust mite allergic asthma in mice has been shown to increase NK, particularly in the mediastinal lymph nodes, but NK blockade by antibodies or their genetic deficiency does not alter the characteristics of asthma, namely Th2 inflammation, bronchial hyperreactivity, specific IgE titers, and mucus production [22]. The study of the prostaglandin I2 receptor deficiency in a HDM allergic murine model shows an increase in IFN-γ producing NK cells in the lungs, inversely correlated with the number of type 2 innate lymphoid cells (ILC2).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, natural killer (NK) cells are a known source of IL-17 that are reported to increase in peripheral blood of patients with asthma (89). However, recent murine studies employing acute and chronic models of HDM-induced airway inflammation demonstrated that NK cells are not necessary for the development of allergen-induced inflammation (90). In summary, additional studies are required to further determine the contributions of eosinophils and NK cells to the development of allergic inflammation.…”
Section: Innate Sources Of Il-17 Contribute To Allergic Inflammationmentioning
confidence: 99%